Frass derived from black soldier fly larvae treatment of biodegradable wastes. A critical review and future perspectives. (1st April 2022) - Lopes, Ivã Guidini; Yong, Jean WH; Lalander, Cecilia
Graphical abstract: Highlights: Black soldier fly (BSF) larvae frass is discussed as a fertilizer. Frass is a biologically unstable organic fertilizer. Frass has multiple plant nutrients and beneficial microorganisms. Frass might be a source of bioactive compounds. Abstract: Inadequately treated biodegradable waste is considered an environmental, social and economic threat worldwide, which call for great attention. Waste treatment with larvae of the black soldier fly (BSF, Hermetia illucens ) complies with the concepts of circular economy, as it enables the transformation of these wastes into marketable products, closing loops and promoting circularity. The processing residues of the treatment (frass) is constantly generated in waste management facilities in large volumes, and this product can be used as an organic fertilizer in agriculture, stimulating a transition to a circular economy. However, many aspects related to frass are still unknown, such as its varying composition of nutrients, microorganisms and bioactive compounds, its post-processing requirements for improved biological stabilization, its behavior in the soil and action in the plants' metabolism, among other aspects. In this review article, we highlight the potential of frass from BSF larvae treatment of biodegradable waste in the world market regarding its possible use as a fertilizer, summarize recent results with this novel product and point towards future research perspectives.